On the Association Between Intention and Visual Word Identification. - Besner, Derek; MacLeod, Colin M. (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2024)
One of the most fundamental distinctions in cognitive psychology is between processing that is "controlled" and processing that is "automatic." The widely held automatic processing account of visualword identification asserts that, among other characteristics, the presentation of a well-formed letter string triggers sublexical, lexical, and semantic activation in the absence of any intention to do so. Instead, the role of intention is seen as independent of stimulus identification and as restricted to selection for action using the products of identification (e.g., braking in response to a sign saying "BRIDGE OUT"). We consider four paradigms with respect to the role of an intention--defined here as a "task set" indicating how to perform in the current situation--when identifying single well-formed letter strings. Contrary to the received automaticity view, the literature regarding each of these paradigms demonstrates that the relation between an intention and stimulus identification is constrained in multiple ways, many of which are not well understood at present. One thing is clear: There is no simple relation between an intention, in the form of a task set, and stimulus identification. Automatic processing of words, if this indeed ever occurs, certainly is not a system default.